Health education in the State of São Paulo, Brazil: conceptions spread between 1917 and 1967 - Maria Cristina, Maria Cristina da Costa Marques; BRASILEIRO, DANILO FERNANDES; João Gusmão, João Oliveira (Historia y Memoria de la Educación, 2021)
The period from 1917 to 1967 was peculiar in the history of public health in São Paulo, Brazil, especially regarding the implementation and consolidation of measures aimed at individual and collective interventions supported by a set of norms and by hygienic rules for changing lifestyle habits, all made possible by numerous health education strategies. This study intends to identify the conceptions of health education that guided the practice of health education between the years 1917 to 1967, in the State of São Paulo. It consists of a review of the scientific literature, consulted in digital databases, from which 214 previously selected articles from a rapid analysis led us to choose 14 articles for the documentary corpus of the study. Most of the 14 selected articles were produced by researchers from São Paulo between 1936 and 2018, when the last article was published. We discovered two categories of analysis that reflect the concepts that underpinned the practice of health education in the State of São Paulo: (1) Health education as an Expression of Biopolitics and (2) Health education as an Expression of Eugenics. We conclude, therefore, that the State of São Paulo used health education as an ally to achieve its goals of building a project of modernity, leading to eugenics and biopolitics as the most compelling expressions of this process